Exploring teacher preparation and teaching content of the Master’s degree programmes in Chinese language teacher education: A case study in China - Zhou, Rui (2017)
The Master of Arts in Teaching Chinese to Speakers of Other Languages (MA TCSOL) programmes have been set up in more than 100 Chinese universities since 2007 (China Academic Degrees & Graduate Education Information, 2010a; Wang, 2013b; Wang, Moloney and Li, 2013). The purpose of this research was to explore teacher preparation and essential teaching content of the MA TCSOL programmes in Chinese language teacher education. This research employed the case study that involved several research methods in order to make an in-depth exploration of the MA TCSOL programmes in two Chinese universities. The data analysis of this research revealed that the teacher preparation of the MA TCSOL programmes in this research was synthetically affected by the craft model, the reflective model, the rationalist model, the case studies model and the integrative model. Based on the participants’ practicum experiences, the results of questionnaires and the participants’ narratives offered insights into the learning outcomes of the MA TCSOL programmes and the challenges or problems in the teaching of Chinese as a foreign language (CFL). The data supported to explore the important and essential knowledge required in CFL teaching, covering Chinese linguistic and cultural knowledge, the knowledge of teaching Chinese as a foreign language (TCFL), second language acquisition theory, teaching skills, English proficiency, intercultural communication and classroom management skills. The